Analisis Kesalahan Berbahasa dalam Pidato Presiden Jokowi di Apel Kader Partai Gerindra (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This study aims to analyze language errors in President Jokowi's speech at the Gerindra Party Cadre Assembly. Using a qualitative descriptive method, the research examines language use from phonological, morphological, syntactic, and semantic aspects. The data source is a speech video uploaded by the Metro TV YouTube account. Data collection used observation methods with note-taking techniques. The research findings reveal various language errors, including phoneme errors, use of non-standard words, pronunciation mistakes, morphological errors in prefix, suffix, and confix usage, as well as syntactic and semantic errors. Nevertheless, the speech remains comprehensible, demonstrating relatively good communication skills.